ANTITUBERCULOSIS POTENTIAL OF Caesalpinia sappan BIOACTIVE COMPOUNDS USING IN SILICO APPROACH - Arafah Nurfadillah; Julianti Bunga; Nur Indah Dg Toba; A Irham Asdar (AL ULUM: JURNAL SAINS DAN TEKNOLOGI, 2026)
Caesalpinia sappan has been reported to possess a plethora of pharmacological effects, including immunomodulatory, antibacterial, astringent, and antitumor properties. The present study set out to ascertain the benefits of the active compounds Caesalpinia sappan in terms of their ability to inhibit the action of the Arabinosyltransferase C enzyme in M. tuberculosis. This research was conducted using an in-silico approach with the following applications: PyMOL, PyRx, AutoDock 4, Biovia Discovery Studio, and Toxtree. The results demonstrated that among the 25 test compounds, gallic acid exhibited the highest Pa value. The gallic acid compound has been found to have the lowest ∆G free bond energy (-7.0 kcal/mol), which is lower than the native ligand and has more hydrogen bonds than the ethambutol. Consequently, gallic acid compounds can impede the function of the Arabinosyl Transferase C receptor.